2018
DOI: 10.18632/oncotarget.25881
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of appropriate pre-analytical procedure for circulating free DNA from liquid biopsy

Abstract: Liquid biopsy with circulating free DNA (cfDNA) is a recommended alternative method of re-biopsy. Quality control with cfDNA is indispensable for precise examinations, and it is desirable to achieve high-quality cfDNA separation. We investigated two issues: the influence of pre-analytical procedures on cfDNA analysis performed as a routine procedure in a standard clinical laboratory, and the extent of deterioration of cfDNA quality due to long-term storage. Comparisons among blood collection tube types, storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Most papers describe cfDNA at size 160-170 bp, and long fragment cfDNA has been thought to be contamination by genomic DNA. We previously reported a pre-analytical procedure for assessing cfDNA, in which we confirmed that long fragment cfDNA appeared in samples stored under inappropriate conditions [8]. However, long fragment cfDNA of 5 Kb was definitely observed in patients with advanced lung cancer even under proper conditions, as described in the present paper and our previous paper [7].…”
Section: Discussionsupporting
confidence: 89%
“…Most papers describe cfDNA at size 160-170 bp, and long fragment cfDNA has been thought to be contamination by genomic DNA. We previously reported a pre-analytical procedure for assessing cfDNA, in which we confirmed that long fragment cfDNA appeared in samples stored under inappropriate conditions [8]. However, long fragment cfDNA of 5 Kb was definitely observed in patients with advanced lung cancer even under proper conditions, as described in the present paper and our previous paper [7].…”
Section: Discussionsupporting
confidence: 89%
“…Increased concentrations could be due to cell lysis that may be a source of pre-analytical error. Additional studies in dogs evaluating the quality as well as the quantity of cfDNA are warranted to determine if citrate plasma maintains cfDNA quality better than does EDTA, as has been described for people 47. Such additional studies might also evaluate whether there is an impact of diagnosis or disease severity on the sensitivity of biomarker detection in distinct sample types.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the use of plasma/serum pools instead of single blood samples for long-term storage experiments might be a good alternative. Recently, it was demonstrated that plasma samples with a low mutant AF degrade faster during storage than samples with a high mutant AF, supporting the assumption that individual samples behave very differently [93]. The storage of extracted cfDNA in a dry form (such as paper-based matrices) as compared to the usual storage in a liquid might be a viable alternative as shown by Heider and colleagues [149].…”
Section: Long-term Storage Of Cell-free Matrices and Freeze-thaw Cyclesmentioning
confidence: 88%
“…In recent years, several companies developed a range of DNA isolation kits of which only the "dedicated" kits were recommended for the extraction of cfDNA [192]. In several papers, a variety of different kits were compared [84,85,93,[193][194][195][196][197][198][199][200][201][202][203][204]. From these results, one can conclude that bead-based isolation methods worked somewhat better than membrane-based kits and that the former ones are especially useful for the isolation of low-molecularweight DNA.…”
Section: Dna Isolationmentioning
confidence: 99%